2007
DOI: 10.1097/01.inf.0000257425.24492.11
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on Pneumococcal Carriage During the First Year of Life in Bangladesh

Abstract: The features found in our study are typical of pneumococcal carriage in developing countries. We believe that results from longitudinal modeling of carriage based on these extensive data can have wide geographic application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 35 publications
7
40
1
1
Order By: Relevance
“…To our knowledge, such very early pneumococcal acquisition has been reported previously only from the highlands of Papua New Guinea, where all children had acquired S. pneumoniae by the age of 3 months [19]. Granat et al [18] showed that 50% of infants acquired a pneumococcus by 8 weeks of age in Bangladesh. In industrialized countries, Gray et al [17] documented a mean time to first acquisition of pneumococci of 6 months in infants in the United States, and Syrjanen et al [20] showed that 34% of Finnish infants had been colonized by S. pneumoniae by 6 months of age and that 56% had been colonized after a year.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, such very early pneumococcal acquisition has been reported previously only from the highlands of Papua New Guinea, where all children had acquired S. pneumoniae by the age of 3 months [19]. Granat et al [18] showed that 50% of infants acquired a pneumococcus by 8 weeks of age in Bangladesh. In industrialized countries, Gray et al [17] documented a mean time to first acquisition of pneumococci of 6 months in infants in the United States, and Syrjanen et al [20] showed that 34% of Finnish infants had been colonized by S. pneumoniae by 6 months of age and that 56% had been colonized after a year.…”
Section: Discussionmentioning
confidence: 88%
“…Although similar longitudinal studies undertaken in both developing and developed countries have shown that most, if not all, children are colonized with pneumococcal strains at some stage during the first 1-2 years of life [17,18], a striking feature of the epidemiology of pneumococcal infection in Gambian villagers is the very early age of first acquisition; the mean and median times to first acquisition were 33 days and 24 days, respectively. To our knowledge, such very early pneumococcal acquisition has been reported previously only from the highlands of Papua New Guinea, where all children had acquired S. pneumoniae by the age of 3 months [19].…”
Section: Discussionmentioning
confidence: 93%
“…Two longitudinal studies undertaken in The Gambia and Bangladesh reported that all children carried S. pneumoniae at least once during their first year of life [49], [50]. In The Gambia, carriage rates increased from 20% within a week of birth to 80%–90% between 3 and 11 months of age [50].…”
Section: Resultsmentioning
confidence: 99%
“…They found a striking degree of concordance for S. aureus colonization between mothers and infants in the first 6 months of life (19). Another study on pneumococcal colonization speculated that newborns mostly obtained their strains from other children rather than from their parents, as the serotype distribution in infants differed from that in adults (9). A Costa Rican study revealed that very few mother-infant pairs carried identical airway pathogens simultaneously (23).…”
mentioning
confidence: 99%